Dynamic Relationship between Exchange Rate of Hang Seng Index and LQ45 Index: Before and During COVID-19 Pandemic - Arfah, Yenni; Gunawan, Didik; Mardayanti, Imelda; Haratikka, Haya; Anggun, Depina (International Journal of Business, Economics & Financial Studies, 2023)
This study determines the relationship between the exchange rate, the Hang Seng index and the LQ45 index using the Vector Error Correction Model (VECM) method. The data used weekly data for 4 years from 2017 to 2020, comprising 208 time series data. The data used in this study is secondary data based on the official website, namely idx.co.id, www.investing.com, wwww.yahoofinance.co.id, bi.go.id. The results of this study indicate that the exchange rate with the LQ45 index had a positive and significant effect on the LQ45 index before and during the COVID-19 pandemic. The Hang Seng index with the LQ45 index had a negative and significant effect on the LQ45 index before the COVID-19 pandemic. The Hang Seng index with the LQ45 index did not affect the LQ45 index during the COVID-19 pandemic. The exchange rate with the Hang Seng index had a negative and insignificant effect on the Hang Seng index before the COVID-19 pandemic. The exchange rate with the Hang Seng index had a positive and significant effect on the Hang Seng index during the Covid-19 pandemic. These findings can assist investors in being more selective in determining whether to buy, sell or hold their shares. The government can make policies related to the exchange rate and maintain the stability of the rupiah exchange rate against the dollar so that the effects can be anticipated and handled as well as possible.